2020
DOI: 10.5465/amj.2017.0420
|View full text |Cite
|
Sign up to set email alerts
|

Should I Stay or Should I Go? Founder Power and Exit via Initial Public Offering

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version.Permanent repository link: https://openaccess.city.ac.uk/id/eprint/21358/ Link to published version: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 180 publications
2
28
0
Order By: Relevance
“…For example, a founder may exit the venture to avoid further losses (despite a reluctance to do so; DeTienne, Shepherd, & De Castro, 2008; Gimeno, Folta, Cooper, & Woo, 1997; Huang et al, 2019). In a recent study, Souitaris, Zerbinati, Peng, and Shepherd (2020) found that founders voluntarily exited their ventures, in full or in part (exited management or ownership), when they became frustrated by a loss in power over the direction of the venture. Managers may also voluntarily exit their ventures as a positive harvest strategy (DeTienne & Cardon, 2012).…”
Section: Methods For Systematic Reviewmentioning
confidence: 99%
“…For example, a founder may exit the venture to avoid further losses (despite a reluctance to do so; DeTienne, Shepherd, & De Castro, 2008; Gimeno, Folta, Cooper, & Woo, 1997; Huang et al, 2019). In a recent study, Souitaris, Zerbinati, Peng, and Shepherd (2020) found that founders voluntarily exited their ventures, in full or in part (exited management or ownership), when they became frustrated by a loss in power over the direction of the venture. Managers may also voluntarily exit their ventures as a positive harvest strategy (DeTienne & Cardon, 2012).…”
Section: Methods For Systematic Reviewmentioning
confidence: 99%
“…Additionally, the power of the founder CEO matters. Souitaris et al (2020), for instance, found a negative relationship between founder CEO power and his or her post‐IPO exit of the firm, and interestingly, they also noted that this relationship is mediated by the extent of frustration experienced by the founder CEO.…”
Section: Founder‐ceo Research Themesmentioning
confidence: 97%
“…Such experiments could be conducted with more readily accessible samples of managers, such as executive education participants or MBA students. There are a handful of recent UET studies that have utilized mixed-methods approaches (e.g., Jung & Shin, 2018; Souitaris, Zerbinati, Peng, & Shepherd, 2020) to leverage the benefits of different research designs. This approach could be an effective way for scholars to respond to endogeneity concerns while also making progress in teasing out important mediators (e.g., Aguinis & Solarino, 2019; Tunarosa & Glynn, 2017).…”
Section: Evaluating Progress Made On Uet Metacritiquesmentioning
confidence: 99%